LASER BEAMS : Near-field focusing of an optical wave by diffraction gratings. (31st July 2016) - Geints, Yu E; Zemlyanov, A A
Abstract: We report the investigation results for spatially-localised light structures (photonic nanojets) under near-field optical radiation scattering on phase diffraction gratings. Main parameters of photonic nanojets from gratings with sawtooth, rectangular and hemispherical groove profiles are obtained by numerical electrodynamic simulation. It is found that by varying a period, degree of filling, groove shape and parameters of optically contrast coating of the diffraction grating one can control the characteristics of the produced photonic jets in a wide range.